Trinidad, B.W.I. - (:unkn) unknown (Unknown, 2011)
A scenic view from a hill overlooking the ocean
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Scenic overlooks; Coasts